Viability of microwave technology for accelerated cold brew coffee processing vs conventional brewing methods. (March 2022) - Caudill, Morgan; Osborne, Jason; Sandeep, K.P.; Simunovic, Josip; Harris, Gabriel Keith
Abstract: Production of cold brew (CB) coffee beverages can require 10–24 h of cold-water infusion. Accelerating this process would facilitate its production on a large scale. This study compared hot brewed coffee (HB), CB, heat-treated CB coffee (H-CB), and microwave treated CB coffee (M-CB) over time in terms of four attributes: color measured by L* values, total dissolved solids (TDS), and mg/100 g caffeine and chlorogenic acid (3-CQA). L* decreased over time for both HB and CB (34.98 → 17.19 vs 64.62 → 43.00), while TDS (0.89 → 1.39 vs 0.29 → 0.85), caffeine (48.90 → 84.39 vs 15.23 → 61.42) and 3-CQA (33.60 → 62.85 vs 5.55 → 44.82) increased. H-CB and M-CB attributes remained constant after the heat treatment (L*, 34.46–35.33 vs 29.23–29.29; TDS, 0.80–1.03 vs 1.00–0.94; caffeine, 56.10–62.21 vs 60.88–69.85; 3-CQA, 39.17–46.00 vs 41.39–49.95), were similar to CB samples, but required less preparation time. A brief heat treatment prior to cold infusion accelerates CB production, allowing industry to develop faster, less costly processing methods. Highlights: Conventional and microwave processing produced similar/comparable results. Analysis of physical and chemical changes in coffee over time. Observed significant separate and interaction effects of time and temperature. Optimization of rapid cold brew processing method.